Effect of C1 Single‐door Laminoplasty on Symptomatic Atlas Canal Stenosis - Linwei Chen; Xiuliang Zhu; Bin He; Qixin Chen; Fangcai Li (Orthopaedic Surgery, 2022)
Objective To verify the effect of single‐door laminoplasty combined with atlantoaxial fusion in the treatment of symptomatic atlas canal stenosis. Methods This is a single‐center retrospective analysis. From February 2014 to January 2019, 16 patients (five were females) with an average age of 63.4 years (56–71 years) were enrolled in this study. Patients with compressive cervical myelopathy with CT scan showed an inner sagittal diameter (ISD) of C1 less than 29 mm or C1 canal space available for cord (SAC) of <12 mm were included, while isolated C1 stenosis without myelopathy or isolated C1 stenosis without atlantoaxial subluxation were excluded in this study. All patients underwent continuous heavy‐weight skull traction, atlas single‐door laminoplasty and atlantoaxial fusion. The differences in the pre‐ and post‐operative inner sagittal diameter, space available for cord, atlas‐dens interval (ADI) and compression of the spinal cord were analyzed by using CT and MRI. Functional evaluation was performed by using the Japanese Orthopaedic Association scoring system and the Neck Disability Index scoring system. Results Single‐door laminoplasty provided a full decompression for the spinal cord while retaining the whole posterior arch. No complications were encountered except a superficial wound infection in one patient. At final follow‐up, The ADI was significantly reduced from 5.2 ± 1.8 mm to 1.7 ± 0.6 mm after surgery on average (P < 0.05). Average inner sagittal diameter of C1 was increased from 26.3 ± 2.6 mm to 34.9 ± 2.9 mm and the space available for cord was increased from 6 ± 1.7 mm to 17.8 ± 3.6 mm (P < 0.05). Meanwhile, the Japanese Orthopaedic Association (JOA) score of the 16 cases was improved from 11.4 ± 1.8 to 14.1 ± 1.4 on average (P < 0.05). The postoperative neck pain VAS score decreased significantly, from 2.6 ± 1.0 preoperatively to 1.3 ± 0.9 postoperatively (P < 0.05). The influence of neck pain on patient's life was improved from 17.8 ± 3.9 to 13.9 ± 3.3 after surgery (P < 0.05). At the last follow‐up, the healing of the hinge fracture and the fusion between atlas and axis were observed in all patients. Conclusions Single‐door laminoplasty combined with atlantoaxial fusion not only provides enough space for decompression but also offers intact arch for bone grafting, suggesting that it might provide a more feasible method for the correction of symptomatic atlas canal stenosis.